Early outcome of radiculopathy with local application of steroid in perineural space in lumbar discectomy - Raihan, Mohammad Farid; Rahman, Asifur; Abu Obaida, Abu Saleh Mohammad; Bari, Md Shahnawaz; Rahman, Md Atikur; Raihan, Hafiz Asif; Razib, Olinur; Bhuiyan, Mohammad Kamruzzaman; Islam, Md Jaynul; Rashid, Mirza Hafizur; Hossain, Mohammad (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Lumbar disc herniation resulting in compression and inflammation of nerve roots causes low back pain and radiculopathy. Per-operative use of steroids may help reduce inflammatory reaction and scar formation, causing less postoperative pain. The study aimed to assess the early outcome of radiculopathy with local application of steroids in peri-neural space after lumbar discectomy. This experimental study was carried out in the Department of Neurosurgery of the National Institute of Neuroscience and Hospital (NINS&H), Dhaka from March 2019 to August 2020. A total of 68 patients operated for prolapsed lumbar intervertebral disc (PLID) at L4/L5 and /or L5/S1 levels were divided into two groups. Patients who did not receive steroids (n=34) and those who received steroids (n=34) in peri-neural space were considered group A and group B, respectively. Patients were examined on the 1st, 2nd and 14th postoperative days to measure the pain intensity by the Visual Analogue Scale (VAS). Pre-operatively mean (standard deviation, sd) VAS was 7.41 (1.28) in Group A and 7.91 (0.9) in Group B (p-value >.05). Mean (sd) improvement of pain intensity on day 1, was 58.82 (17.55)% in Group A and 70.59 (12.26)% in Group B from pre-operative VAS. On day 2, 71.69 (12.43)% improvement was seen in Group A and 79.78 (9.74)% in Group B. On day 14, 75.37 (9.96)% improvement was seen in Group A and 83.46 (7.36)% in Group B from pre-operative. The improvements of VAS in all 1st, 2nd and 14th days were statistically significant (p-value <.05) between the two groups. Local application of steroids in peri-neural space found effective in reducing early postoperative radiculopathy following lumbar discectomy. BSMMU J 2022; 15(2): 107-109